2020
DOI: 10.3390/ijerph17031008
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Rotavirus Infection Surveillance: Epidemiological Trends in the Pediatric Population of Perugia Province

Abstract: Rotavirus (RV) infections are a leading cause of severe gastroenteritis in children, and vaccination is currently recommended in Italy, according to the National Immunization Plan 2017–2019. The objective of this study was to describe the epidemiological and molecular RV surveillance in the pediatric population of Perugia province, Umbria. Between September 2007 and August 2018, 663 RV-positive stool specimens were collected from children <15 years of age presenting with gastroenteritis to the emergency roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
4
1
Order By: Relevance
“…33 Globally G9 genotype is commonly being circulated in combination with P [8] which is different from our study. [34][35][36][37] In the current study, G1 genotype was detected in 22.3% cases and is found in combination with P [4], P [6], and P [8]. G1P [8] genotype was detected in 19% cases during 2018-2020 that dropped to 15.7% in 2020 from 23.6% in 2019.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…33 Globally G9 genotype is commonly being circulated in combination with P [8] which is different from our study. [34][35][36][37] In the current study, G1 genotype was detected in 22.3% cases and is found in combination with P [4], P [6], and P [8]. G1P [8] genotype was detected in 19% cases during 2018-2020 that dropped to 15.7% in 2020 from 23.6% in 2019.…”
Section: Discussionsupporting
confidence: 45%
“…13,18,20,24 Moreover, the proportion of G1P [8] circulating is low in other countries like Italy, India, USA, Australia, Africa, and Europe. 27,37,38 Globally, decline in G1P [8] 31 but interestingly in current study, substantial drop in G2P [4] has observed from 11.5% in 2018 to 2.4% in 2020. These results may negate the Rotarix vaccine pressure associated G2P [4] predominance.…”
Section: Discussionmentioning
confidence: 44%
“…Rotavirus A infections are reported to be the leading cause of severe acute gastroenteritis in young children and infants worldwide ( Gupta et al, 2019 ; Damtie et al, 2020 ; Waure et al, 2020 ); however, in Cape Verde, vaccination against RVA is not included in the national vaccination calendar. The results for RVA infection obtained in this study are in line with those reported in different countries, mainly in poor or developing countries; for example, in a study carried out in Taiwan, RVA remained the main cause of viral gastroenteritis that requires hospitalization in children, even after vaccine implementation, but at a much lower rate (43 and 46–21.2%) ( Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…About one in every three adult infections is clinically inapparent, although reinfection in both children and adults does occur [ 30 , 60 ]. Boys infected with rotavirus are more likely than girls to be admitted to the hospital [ 160 ]. The reason for this difference has not yet been proven.…”
Section: Epidemiology and Molecular Diversitymentioning
confidence: 99%